Precedentes como instrumento de coletivização da lide - Rollo, Luiz Gustavo de Almeida (2020)
The massification of behaviors or even the transindividual consequences of certain legal facts affect the Judiciary and create phenomena such as mass or repetitive causes. The adoption of procedures such as the incident of resolution of repetitive demands, the incident of assumption of competence and the maintenance of the rite of judgment of repetitive appeals brought a change to collective actions, subjecting these demands to the decisions taken within such procedures. Laws dealing with homogeneous individual rights, the main source of repetitive causes, are now under the protection of those decided in these procedures for setting the legal thesis, thus losing part of the functions established by the legal texts that form the collective procedural microsystem. They are, therefore, subject, like any other individual action, to the fetters of the precedent set for application in all actions that have the same object or the same question of law and fact, preventing the functioning of instruments that ensured an advantage to the collective process. The reflexes that such devices will have on the collective actions in such demands and their consequences make up the object of this work